1980
DOI: 10.1017/s0031182000061898
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the development and survival of the free-living stages of Oesophagostomum dentatum both in their natural environments out-of-doors and under controlled conditions in the laboratory

Abstract: SUMMARYEggs of Oesophagostomum dentatum in faeces deposited on grass plots from May to October developed into infective larvae. Warm wet weather facilitated development but weather conditions which caused the faeces to dry out rapidly resulted in a heavy mortality of eggs and pre-infective larvae. During the winter no development took place and the eggs died. In the early spring and late autumn a few eggs survived and developed into 1st-stage larvae but they died without developing further. In the laboratory n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 5 publications
4
12
0
Order By: Relevance
“…week 24, a reduced survival rate of the larvae, especially at 158C, was observed. Similar studies on larval survival have been made on the closely related nematodes Trichostrongylus colubriformis and Hyostrongylus rubidus (Rose & Small, 1982, 1984 whereby survival rates dropped dramatically between weeks 16 and 24 at 228C and 278C, respectively. Larvae utilize lipids as their primary energy source and the dramatic change in survival rate after 16 weeks is likely to be due to the exhaustion of food reserves.…”
Section: Discussionsupporting
confidence: 61%
“…week 24, a reduced survival rate of the larvae, especially at 158C, was observed. Similar studies on larval survival have been made on the closely related nematodes Trichostrongylus colubriformis and Hyostrongylus rubidus (Rose & Small, 1982, 1984 whereby survival rates dropped dramatically between weeks 16 and 24 at 228C and 278C, respectively. Larvae utilize lipids as their primary energy source and the dramatic change in survival rate after 16 weeks is likely to be due to the exhaustion of food reserves.…”
Section: Discussionsupporting
confidence: 61%
“…The fact that the EPG remained fairly constant and that no larvae of any of the two species were detected in any sample set up at 5°C at any time during the study period (70 days), indicated that the eggs did not hatch at this temperature. This finding corresponds well with previous studies which have indicated that no development takes place below 5°C either by H. rubidus (Rose & Small, 1982) or Oesophagostomum spp. (Rose & Small, 1980 1986).…”
Section: Discussionsupporting
confidence: 93%
“…This finding corresponds well with previous studies which have indicated that no development takes place below 5°C either by H. rubidus (Rose & Small, 1982) or Oesophagostomum spp. (Rose & Small, 1980 1986). Eggs persisted for a longer period, and the larval recovery was significantly lower at 10°C compared to the higher temperatures.…”
Section: Discussionsupporting
confidence: 93%
“…Infection is thought to occur via ingestion of L3 within contaminated water, soil, or food. Studies of Oesophagostomum dentatum have demonstrated survival of infective larvae within the environment for up to or greater than 1 year depending on humidity, temperature, and foliage [Rose & Small, ; Waruiru et al, ]. After ingestion, L3 burrow into the intestinal wall and form nodules within which they develop to fourth‐stage larvae (L4).…”
Section: Introductionmentioning
confidence: 99%